2011
DOI: 10.1038/aps.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

Propofol increases the Ca2+ sensitivity of BKCa in the cerebral arterial smooth muscle cells of mice

Abstract: Aim: Propofol has the side effect of hypotension especially in the elderly and patients with hypertension. Previous studies suggest propofol-caused hypotension results from activation of large conductance Ca 2+ -sensitive K channels (BKCa). In this study, the effects of propofol on the Ca 2+ sensitivity of BKCa were investigated in mice cerebral arterial smooth muscle cells. Methods: Single smooth muscle cells were prepared from the cerebral arteries of mice. Perforated whole-cell recoding was conducted to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Activation of BK Ca channels elicits the infarct-sparing effects of late ischemic preconditioning in myocardial I/R injury in animal models ( Wang et al, 2010 ). Liu X.R. et al (2012) suggested that propofol causes greater vasodilating effects by increasing the Ca 2+ sensitivity of BK Ca channel in the cerebral arterial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of BK Ca channels elicits the infarct-sparing effects of late ischemic preconditioning in myocardial I/R injury in animal models ( Wang et al, 2010 ). Liu X.R. et al (2012) suggested that propofol causes greater vasodilating effects by increasing the Ca 2+ sensitivity of BK Ca channel in the cerebral arterial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The development of chronic hypertension could be attributed to the decrease in blood vessel elasticity induced by long-term excessive contraction [ 4 ]. Under such a pathophysiological condition, propofol, with its potent vasodilative effect, can switch the state of blood vessels from overcontraction to excessive relaxation [ 5 ]. Eventually, patients with chronic hypertension have abrupt fluctuations in blood pressure and usually experience long-term hypotension because of the deterioration of vascular elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with vena cava collapse are prone to develop significant hypotension when treated with propofol, which may be a direct result of vascular relaxation ( 1 4 ). Certain studies have indicated that propofol elicits vascular relaxation via the following mechanisms: i) Activation of large-conductance calcium voltage-activated potassium channels (BK Ca ) ( 2 ); ii) activation of ATP-sensitive K + channels (K ATP ) ( 5 ); iii) inhibition of voltage-operated calcium channels and receptor-operated calcium channels ( 6 ); and iv) increases in the availability of nitric oxide ( 7 , 8 ). Propofol may cause vasodilation via four different pathways, however, to the best of our knowledge, no experimental study has assessed the mechanism of vasodilation induced by propofol on the rat mesenteric artery.…”
Section: Introductionmentioning
confidence: 99%